Angola : Second Review of the Extended Arrangement Under the Extended Fund Facility, Requests for a Waiver of Nonobservance of Performance Criteria, Modifications of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Angola's Second Review of the Extended Arrangement Under the Extended Fund Facility, Requests for a Waiver of NonObservance of Performance Criteria, Modifications of Performance Criteria, and Financing Assurances Review. Angola continues to face a deteriorated external environment, which is weighing on the economic outlook. The Angolan authorities have maintained their commitment to the Fund-supported program despite a challenging external and domestic environment. The authorities' commitment to fiscal consolidation has been illustrated by the outperformance of the end-June 2019 non-oil primary fiscal deficit target by a wide margin. Sustained fiscal discipline is needed to address debt vulnerabilities. The conservative fiscal stance is expected to continue in 2020. In order to ensure that gains from fiscal consolidation will be preserved in the medium term and to mitigate the elevated risks to debt sustainability, the authorities need to persevere with measures to mobilize non-oil revenue, strengthen public financial management, improve debt management, and bolster transparency and accountability of state-owned enterprises.